EFFECT OF HPMC/CARBOPOL ON THE RELEASE OF CHLORPHENIRAMINE MALEATE FROM MATRIX TABLETS - Bipin P. Patel; Dasharath M. Patel; Jayvadan K. Patel (Indonesian Journal of Pharmacy, 2013)
Chlorpheniramine maleate is widely used in treatment for allergic disorder and cold. The controlled release matrix tablets of chlorpheniramine maleate were prepared using HPMC K15M, HPMC K100M and carbopol and studied their effect on drug release. Prepared tablets were evaluated for various physical parameters. In vitro drug release study shows that slow release in HPMC K100M than other two polymers. If concentration of polymer increases than the drug release is decreases due to formation of polymeric matrix. Zero order, first order, Higuchi’s and Korsmeyer’s equations applied to know the mechanism of drug release from prepared tablets. The similarity and dissimilarity factor found to be 77.88 and 4.14, respectively for drug release in stability study which shows there was no significant difference in drug release.Key words: Chlorpheniramine maleate, matrix tablet, HPMC K15M, HPMC K100M, carbopol and swelling index